PENGEMBANGAN POTENSI WISATA EDUKASI OLEH LEMBAGA MASYARAKAT DESA HUTAN (LMDH) MELALUI KONSEP PENTA-HELIX DI KAWASAN GEOWISATA KAWAH WAYANG DESA SUKAMANAH KECAMATAN PANGALENGAN - Rendy Adiwilaga; Nisrina Salsabila (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to analyze the application of the pentahelix model in the development of educational tourism potential of Wayang Crater, Sukamanah Village, Pangalengan District. This type of research is descriptive with a qualitative approach. The informants in this study were the Village Head of Sukamanah, LMDH Sukamanah, Visitors of Wayang Crater Tour, PT. Star Energy. Data were obtained by conducting observations, interviews with informants and literature studies. The results of the study indicate that business, community, government and media play a role in developing the potential for educational tourism at Kawah Wayang. The government through BUMDES plays a major role in development, especially as the main investor. Likewise, LMDH as the manager has played the most dominant role in developing the potential of Wayang Crater Educational Tourism. The media has been involved in the development but has not been maximized and must be improved so that the promotion can be conveyed to the public in detail. The implication in this research is that in the future the academy can play a role in the development of Wayang Crater Educational Tourism because the academics as researchers and study experts are to make Wayang Crater tourism more competitive.